Duramater Healing Following Decompression And Posterior Stabilization Using Platelet Rich Plasma And Platelet Rich Fibrin: A Systematic Review - Kennedy, Dave; Arifin, Jainal; Nathaniel, Dave Gilbert (South Eastern European Journal of Public Health, 2024)
Background: Platelet-rich plasma (PRP) applications have the potential to play adjunctive roles in a variety of regenerative medicine treatment plans. PRP therapy is based on the fact that platelet growth factors (PGFs) support the three phases of wound healing and repair cascade. This systematic review evaluates the efficacy of platelet-rich plasma (PRP) and platelet-rich fibrin (PRF) in enhancing duramater healing and reducing complications, particularly cerebrospinal fluid (CSF) leaks, following spinal surgeries. Incidental dural tears are a common complication in lumbar spine surgeries, leading to significant postoperative challenges. Methods: The review included randomized controlled trials comparing PRP and PRF with conventional treatments, sourced from databases such as PubMed, ScienceDirect, ProQuest, and Cochrane Library. Results: PRP and PRF are rich in growth factors such as platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and transforming growth factor-beta (TGF-β), all of which play crucial roles in wound healing. Conclusion: Both PRP and PRF significantly improve duramater healing, with PRF offering a more sustained release of growth factors, thereby enhancing watertight dura closure and reducing CSF leakage.